2022
DOI: 10.3390/ijms232113587
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-381 Regulates Proliferation and Differentiation of Caprine Skeletal Muscle Satellite Cells by Targeting PTEN and JAG2

Abstract: In our previous study, microRNA (miR)-381 was found to be the most down-regulated miRNA in skeletal muscle of Liaoning cashmere goats with higher skeletal muscle mass, but the molecular mechanism involved remains unclear. In this study, primary caprine skeletal muscle satellite cells (SMSCs) were isolated and identified. We investigated the effect of miR-381 on the viability, proliferation and differentiation of caprine SMSCs, and the target relationships of miR-381 with jagged canonical Notch ligand 2 (JAG2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…We conducted Gene Ontology (GO) enrichment analysis on the target gene candidates of differentially expressed miRNAs. For Gene Ontology (GO) enrichment analysis, we employed a Wallenius non-central hypergeometric distribution based on GOseq 23 , which can adjust for gene length bias. KEGG 24 is a database resource for inferring high-level functions and utilities of biological systems such as the cell, organism, and ecosystem from molecular-level data, especially large-scale molecular datasets generated by genome sequencing and other high-throughput experimental technologies ( http://www.genome.jp/kegg/ ).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted Gene Ontology (GO) enrichment analysis on the target gene candidates of differentially expressed miRNAs. For Gene Ontology (GO) enrichment analysis, we employed a Wallenius non-central hypergeometric distribution based on GOseq 23 , which can adjust for gene length bias. KEGG 24 is a database resource for inferring high-level functions and utilities of biological systems such as the cell, organism, and ecosystem from molecular-level data, especially large-scale molecular datasets generated by genome sequencing and other high-throughput experimental technologies ( http://www.genome.jp/kegg/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Shen et al . found that Pten positively regulates the proliferation of skeletal muscle satellite cell [ 20 ]. Firstly, the function of Pten regulation on myoblast proliferation was confirmed mediated by si- Pten treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A certain degree of autophagy helps cells with repair and regeneration, while excessive autophagy has a negative effect on cell function and can lead to cell apoptosis 18 . SMSCs are myogenic stem cells with proliferation and differentiation capabilities after injury or stimulation by certain factors 19 . At present, there is evidence that autophagy can regulate the differentiation of SMSCs 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%